2013
DOI: 10.1177/0731684413512706
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the seismic behavior of reinforced concrete beam-column joints under various strain rates

Abstract: The reinforced concrete beam-column joint exhibits different properties under dynamic loading when compared with that under quasi-static loading, due to the effect of strain rate. However, the majority of previous studies are focused more on the rate effect of concrete and reinforcement, but less on beam-column joints. Based on the former considerations, the seismic behavior of 15 cruciform specimens subjected to various strain rates is studied in this paper, aimed at attaining a better understanding of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…There have been a limited number of past studies that have experimentally investigated the effects of loading rate on the cyclic behavior of ductile reinforced concrete components, by testing otherwise identical specimen pairs or sets at both static and dynamic speeds . Aside from a consistent increase in peak strength due to dynamic loading, the results from these test programs were varied.…”
Section: Previous Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…There have been a limited number of past studies that have experimentally investigated the effects of loading rate on the cyclic behavior of ductile reinforced concrete components, by testing otherwise identical specimen pairs or sets at both static and dynamic speeds . Aside from a consistent increase in peak strength due to dynamic loading, the results from these test programs were varied.…”
Section: Previous Researchmentioning
confidence: 97%
“…There have been a limited number of past studies that have experimentally investigated the effects of loading rate on the cyclic behavior of ductile reinforced concrete components, by testing otherwise identical specimen pairs or sets at both static and dynamic speeds. [20][21][22][23] Aside from a consistent increase in peak strength due to dynamic loading, the results from these test programs were varied. However, two tendencies were identified for the majority of the dynamically loaded specimens, relative to the static specimens: (1) percentage strength increases were largest at, or near, the yield point and (2) slightly faster decay in lateral stiffness or resistance and reduced deformation capacities.…”
Section: Effects Of Loading Ratementioning
confidence: 99%
“…The paper concluded that the loading rate has a considerable influence on the overall shape of hysteresis curves; fast cyclic tests resulted in an asymmetric response, while slow cyclic tests resulted in an antisymmetric behavior. In contrast, other studies demonstrated that loading rates expected during earthquakes have no influence on the overall shape of the load-deflection response (Fan et al 2014;Li and Li 2012;Ghannoum et al 2012;Gutierrez et al 1993). We think that this discrepancy can be explained if specimento-specimen variability in the fast tests presented in the paper is considered in evaluating the results.…”
mentioning
confidence: 68%
“…On average, the amount of strength reduction was 7.4% and 7.6% for the maximum strength obtained in the positive and negative cycles, respectively. Other studies, however, reported that as the loading rate increases, the strength of RC members improves (Fan et al 2014;Li and Li 2012;Ghannoum et al 2012;Lamarche et al 2011;Gutierrez et al 1993;Reinschmidt et al 1964). The level of strength gain in the majority of these studies was about 10%, which was considerably lower than that observed at the material level (Malvar 1998;Malvar and Ross 1998).…”
mentioning
confidence: 96%
“…Because of the difficulty in axial force control, most existing studies with axially stiff members do not discuss the accuracy of their axial force control. It is difficult to check if the target axial force was satisfactorily controlled with a fast loading rate in the studies by Gutierrez et al (1993) and Fan et al (2014). The study by Li and Li (2012) was for beam structures that do not have axial force.…”
mentioning
confidence: 99%